Estudios sobre el África romana : culturas e imaginarios en transformación - Salcedo, Fabiola; Lázaro, Estefaniá Benito; España-Chamorro, Sergio; Archaeopress (Summertown, Oxford : Archaeopress Publishing Ltd, 2018)
These collected papers are for those who have their gaze fixed on the fascinating mosaic of cultures that was the North-African world from the moment Rome appeared in the region. Most articles are dedicated to the world of images, but other subjects include Historiography, Archaeology of Architecture, and Libyan-Berber ethnicities.
Prólogo; Preface (in English); Agradecimientos; Principales repertorios utilizados; Arqueología y cuestiones historiográficas: La investigación arqueológica en el Magreb: fabricando identidades (El caso de Túnez) -- by Nayra Bethencourt González; Las exploraciones arqueológicas del conde Byron Khun de Prorok en África -- by Jorge García Sánchez; Aproximación a la compleja historia arquitectónica de las Termas de Antonino Pío en Cartago -- by Julio Núñez, Mitxel Salazar, Carlos Pérez, Oscar Reinares; L'Antiquité dans le Ribat de Monastir: les chapiteaux et les corbeaux -- by Ahmed Sayadi; Líbicos y púnicos en el África romana: Los pueblos líbicos del norte de África: territorio, conceptos, fuentes -- by Estefanía A. Benito Lázaro; Sincretismo, alteridad y polisemia en el relieve de las siete divinidades líbico-púnicas de Béja (Túnez) -- by Beatriz Calvo Bartolomé; Hic sunt Musulami. Desterritorialización, pueblos y límites en el África romana. El caso de los musulamios -- by Sergio España-Chamorro; El sarcófago antropoide masculino del Museo Nacional de Cartago: algunas consideraciones -- by Raquel Rubio González, M. Inmaculada Martín Martín; El sacrificio animal en las estelas neopúnicas del norte de África -- by Azael Varas Mazagatos; Survivances de croyances et de rituels puniques: à propos de quelques figurines en terre cuite, de tradition punique, de la région d'El Jem -- by Samia Zeghal-Yazidi; Roma en África: Clásico y anticlásico en el imaginario del África romana -- by Fabiola Salcedo Garcés; Los relieves de Victorias del Museo Nacional de Cartago (Túnez) -- by Raquel Rubio González; Retratos femeninos de Cartago -- by Paloma Mora Bernaldo de Quirós; El Relieve de las Ménades de Thuburbo Maius (Túnez) -- by Macarena Calderón Sánchez, Irene de Lucas Clemente; La identidad de Saeculum Frugiferum: ¿divinidad o alegoría? -- by Silvia Bonacasa Sáez; Saturno Africano. Cuestiones sobre imagen y culto -- by Mónica Galea González, Azael Varas Mazagatos; Cultos orientales en el África romana: el caso de Cibeles -- by Erika Rodríguez Angulo; Iconografía de Iuno Caelestis: estado de la cuestión -- by Beroiz von Kursell Pérez de Rada; Entre Cartago y Roma: ejemplos de la cerámica ibérica pintada figurada -- by Juan A. Santos Velasco.
Previously issued in print: 2018.
Specialized.
Online resource; title from home page (viewed on October 4, 2018).
Available through Archaeopress Digital Subscription Service.
Includes bibliographical references.
Articles in Spanish or French, with English abstracts.
Keywords: Africa, North -- History -- To 647.; Africa, North -- Antiquities, Roman; Africa, North -- Civilization; Berbers -- Africa, North -- Social life and customs; Afrique du Nord -- Histoire -- Jusqu'à 647.; Afrique du Nord -- Antiquités romaines; Berbères -- Afrique du Nord -- Mœurs et coutumes; SOCIAL SCIENCE / Archaeology; Berbers -- Social life and customs; Civilization; Classical antiquities; North Africa; Berber; Kulturkontakt; Römer; Africa; Africa (region); To 647; History